Smarter vaccine design will circumvent regulatory T cell-mediated evasion in chronic HIV and HCV infection - Moise, Leonard; Terry, Frances; Gutierrez, Andres H.; Tassone, Ryan; Losikoff, Phyllis; Gregory, Stephen H.; Bailey-Kellogg, Chris; Martin, William D.; De Groot, Anne S. (Frontiers in Microbiology, 2014)
Despite years of research, vaccines against HIV and HCV are not yet available, due largely to effective viral immunoevasive mechanisms. A novel escape mechanism observed in viruses that cause chronic infection is suppression of viral-specific effector CD4+ and CD8+ T cells by stimulating regulatory T cells (Tregs) educated on host sequences during tolerance induction. Viral class II MHC epitopes that share a TCR-face with host epitopes may activate Tregs capable of suppressing protective responses. We designed an immunoinformatic algorithm, JanusMatrix, to identify such epitopes and discovered that among human-host viruses, chronic viruses appear more human-like than viruses that cause acute infection. Furthermore, an HCV epitope that activates Tregs in chronically infected patients, but not clearers, shares a TCR-face with numerous human sequences. To boost weak CD4+ T cell responses associated with persistent infection, vaccines for HIV and HCV must circumvent potential Treg activation that can handicap efficacy. Epitope-driven approaches to vaccine design that involve careful consideration of the T cell subsets primed during immunization will advance HIV and HCV vaccine development.